Pengabdian Kepada Masyarakat Melalui Penyuluhan Perilaku Hidup Sehat Kota Batam - Suhaera Suhaera; Ghalib Syukrillah Syahputra; Aprilya Sri Rachmayanti; Henny Rachdianti Tjahjono Suyarto (Pusat Riset dan Inovasi Nasional, 2021)
Batam City faces health problems related to lifestyle, such as obesity, diabetes, hypertension and heart disease. This can be caused by unhealthy eating patterns, lack of physical activity, as well as smoking and alcohol consumption. Counseling about the importance of a healthy lifestyle is important to reduce morbidity and mortality due to this disease. Healthy Living Behavior Counseling in Batam City not only aims to increase people's knowledge about healthy eating patterns and the importance of exercise, but also to change their attitudes and behavior in daily practice. Through outreach that is held systematically and continuously, it is hoped that the people of Batam City can understand the positive impact they will experience by adopting a healthy lifestyle.